2022
DOI: 10.3390/s22176378
|View full text |Cite
|
Sign up to set email alerts
|

A Novel High-Speed Resonant Frequency Tracking Method Using Transient Characteristics in a Piezoelectric Transducer

Abstract: When driving the piezoelectric transducer (PT: piezo transducer), which is a key device, it is important for the ultrasonic system (using ultrasonic waves of 20 kHz or higher) to operate at a resonant frequency that can maximize the conversion of mechanical energy (vibration) from electrical energy. The resonant frequency of the PT changes during the actual operation according to the load fluctuations and environmental conditions. Therefore, to maintain a stable output in an ultrasonic system, it is essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Usually, the pure PLL phase control tracking method is only used to track the local resonant frequency, but not suitable for large frequency range sweep tracking [15] , [174] , [179] . Other methods (including the maximum current method [182] , maximum power method [183] , self-sensing model method [184] , composite tracking method [106] , etc.) can usually perform both global sweep frequency tracking and local resonance frequency tracking.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the pure PLL phase control tracking method is only used to track the local resonant frequency, but not suitable for large frequency range sweep tracking [15] , [174] , [179] . Other methods (including the maximum current method [182] , maximum power method [183] , self-sensing model method [184] , composite tracking method [106] , etc.) can usually perform both global sweep frequency tracking and local resonance frequency tracking.…”
Section: Discussionmentioning
confidence: 99%
“…This design was responsible for maintaining the sensor’s resonant frequency at a predetermined value, which enables accurate pressure measurements 97 . Various techniques, including the frequency locking technique 98 , 99 , phase-locked loop (PLL) technique 100 104 , adaptive control technique and digital control technique 105 , 106 , and proportional-integral-derivative (PID) control technique 74 , 77 , 94 , 107 , have been developed to drive mechanical motion, control feedback, and track frequency changes. For the circuit design described above, establishing the equivalent circuit model of an RPS provides an important foundation for sensor characterization and closed-loop circuit design.…”
Section: Rpsmentioning
confidence: 99%
“… a Schematic of the closed-loop circuit with automatic gain control 100 . b Schematic view of the oscillator and the frequency response of the loop gain 101 .…”
Section: Rpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical and experimental studies reported by Piquette showed that, under the excitation of a sinusoidal voltage signal, the dynamical state on the surface of a piezoelectric transducer went through a transient transition process from a static state to a steady state sinusoidal vibration [ 52 , 53 ]. Moon et al found that the resonant frequency of the piezoelectric transducer changed with the load’s fluctuations and environmental conditions and proposed a method to track the resonant frequency using the transducer’s transient characteristics [ 54 ]. Wang et al investigated the relationship between eigenfrequency and the early strength development of cement mortar by using a piezoelectric transducer [ 55 ].…”
Section: Introductionmentioning
confidence: 99%